THE IMPLEMENTATION OF GOVERNOR INDONESIAN NAVAL ACADEMY’ POLICY FOR DEVELOPING OF LOKA JALA CRANA - Suhendra Suhendra; Budi Rianto; Ninis Trisyanti (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
The existence of the Loka Jala Crana Museum is currently a place for tourism education, research and a source of information about the history of the Navy. is a place to store and preserve historical objects, so that historical objects are maintained. There are so many positive activities that can be done at the museum. For the public and students who uphold it, they can enjoy educational tours, as well as opportunities to learn about the history. Museums are not just a place to enjoy collections, but museums can also be a means of holding creations, education, research, information, innovation and recreation/educational tours for visitors. The use of Naval Academy educational facilities as educational tourism objects is part of the integrity zone of bureaucratic reform in the field of public services that supports government programs. This study concludes that the Loka Jala Crana museum as an educational tourism destination for the theory of implementation of the George C. Edward III model has been carried out optimally. From this research, it is suggested that the recommendations are. The placement of personnel in the Museum should be based on qualifications/experts in the field of museums, history, anthropology and sociology, not just to fulfill the number of personnel lists. The need to improve human resource education about museums is the point of the need to increase the budget, infrastructure and facilities of the Loka Jala Crana museum. Keywords: Policy Implementation, Service at The Loka Jala Crana Museum as A Means of Educational Tourism